A method of identifying small angle grain boundaries in sesquioxide crystals
Patent Information
- Application Number
- CN202511347183.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-19
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-09-19
AI Technical Summary
这一过程不仅操作繁琐、耗时较长,还会引入表面污染、改变晶体表层结构,甚至造成不可逆的损伤,影响后续加工与性能表征
本发明提供了一种识别倍半氧化物晶体小角晶界的方法,通过物理机械加工与光学观察相结合实现倍半氧化物晶体晶界的快速识别。具体的:
Smart Images

Figure CN121253518B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of crystal detection technology, specifically relating to a method for identifying small-angle grain boundaries in sesquioxide crystals. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Sesquioxide crystals (such as Lu₂O₃, Sc₂O₃, and Y₂O₃) exhibit significant application potential in fields such as lasers and scintillation devices due to their high thermal conductivity, low phonon energy, and strong crystal field. However, the extremely high melting point and difficulty in controlling the thermal gradient during the growth of these crystals easily lead to defects such as grain boundaries and inclusions, severely affecting their electrical and optical properties. Therefore, developing a method for rapid and accurate identification of grain boundaries is of great significance for evaluating crystal quality and selecting optimal single-crystal regions.
[0004] Most commonly used grain boundary detection methods involve complex sample pretreatment processes, particularly the chemical etching of crystals to expose grain boundaries. For example, before employing techniques such as X-ray diffraction (XRD), electron backscatter diffraction (EBSD), high-resolution transmission electron microscopy (HRTEM), and three-dimensional X-ray diffraction (3D-XRD) imaging, samples typically require polishing and chemical etching to eliminate surface stress and highlight grain boundary features. This process is not only cumbersome and time-consuming but also introduces surface contamination, alters the crystal surface structure, and can even cause irreversible damage, affecting subsequent processing and performance characterization. Furthermore, while high-resolution transmission electron microscopy (HRTEM) can directly observe grain boundaries, sample preparation is more complex, often requiring a combination of focused ion beam (FIB) processing and etching steps, resulting in high sample preparation costs and low success rates, making it unsuitable for rapid screening of large-sized crystals.
[0005] Therefore, developing a simple, low-cost, and widely applicable method for grain boundary identification has become an urgent technical problem to be solved in this field. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a method for identifying small-angle grain boundaries in sesquioxide crystals. This invention places the processed crystal surface under bright light, which can quickly reveal the macroscopic location of the grain boundaries. It has the advantages of simple operation, low cost, rapid identification, macro-micro integration, and intuitive and reliable results.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows: A first aspect of the present invention provides a method for identifying small-angle grain boundaries in sesquioxide crystals, comprising: The crystal surface is processed to control the roughness (Sa) within 0.7-2 μm; Place the crystal surface to be tested under a light source and shake it. Observe with the naked eye; the boundary between the light and dark areas is the grain boundary.
[0008] This invention controls the crystal surface processing to form a crystal surface with a specific roughness (Sa=0.7-2 μm), so that the grain boundaries appear as visible partitions under a bright light source due to differences in light scattering. This avoids the use of complex detection equipment such as traditional TEM and FIB, and is suitable for the rapid identification of grain boundaries of high melting point sesquioxide crystals such as Lu2O3, providing immediate guidance for the optimization of crystal growth processes.
[0009] In some embodiments of the present invention, the crystal surface processing method includes: cutting along a direction parallel to the surface to be tested to obtain a sample to be tested.
[0010] In some embodiments of the present invention, the cutting is diamond wire cutting with a wire diameter of 0.2-0.35 mm, a cutting speed of 0.2-0.3 mm / min, and a rotational speed of 260 rps.
[0011] In some embodiments of the present invention, the crystal surface processing method includes: performing wet grinding on the crystal to be tested to obtain the sample to be tested.
[0012] In some embodiments of the present invention, the rotational speed of the wet grinding is 100-200 rpm. In some embodiments of the present invention, the particle size of the abrasive is 1-5 μm.
[0013] In some embodiments of the present invention, the abrasive is silica abrasive or alumina abrasive.
[0014] In some embodiments of the present invention, the illuminance of the light source is ≥500 lx.
[0015] In some embodiments of the present invention, the crystal is a sesquioxide crystal.
[0016] In some embodiments of the present invention, the crystal is a sesquioxide crystal including Lu2O3, Sc2O3, Y2O3 and their doped crystal systems.
[0017] The beneficial effects of this invention are as follows: This invention provides a method for identifying small-angle grain boundaries in sesquioxide crystals, achieving rapid identification of grain boundaries through a combination of physical mechanical processing and optical observation. Specifically: 1. No chemical etching required, simple operation and minimal damage. This method directly obtains a crystal surface with a specific roughness through controlled machining, completely avoiding the surface contamination and structural damage caused by traditional chemical etching methods. It is a grain boundary identification method with extremely low destructiveness, which is beneficial for subsequent wafer processing and device fabrication.
[0018] 2. Low equipment requirements and significant cost savings. This invention only requires conventional cutting or grinding equipment, eliminating the reliance on large precision instruments such as XRD, EBSD, HRTEM, or synchrotron radiation sources, greatly reducing testing costs and barriers, and making it more conducive to industrialization and application.
[0019] 3. High detection efficiency and rapid macroscopic positioning. This invention can rapidly detect large-sized crystal surfaces, enabling in-situ, real-time observation of grain boundaries. It overcomes the limitations of methods such as electron microscopy, which have small fields of view and slow scanning speeds. It is suitable for rapid screening and regional selection of crystal quality in production line environments.
[0020] 4. The identification results are intuitive and facilitate subsequent processing. Utilizing the light and dark contrast formed by differences in crystal orientation on a specific rough surface, the macroscopic location of grain boundaries on the sample surface can be quickly, clearly, and intuitively revealed under the naked eye, facilitating large-scale screening and preliminary localization. The clear and intuitive images provide a reliable basis for directional cutting of high-quality single-crystal regions. This significantly reduces the long and costly scanning or 3D reconstruction time required by traditional electron microscopy or synchrotron radiation methods.
[0021] 5. It has good universality and repeatability. The method of this invention identifies crystals based on their intrinsic anisotropy, without introducing chemical modification. The results are stable and reliable, and it is applicable to a variety of sesquioxide crystals, including lutetium oxide, thus possessing high method versatility. Attached Figure Description
[0022] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0023] Figure 1 The results show the surface roughness test results of the Lu2O3 crystal sample in Example 1 of this invention.
[0024] Figure 2 The image shows grain boundaries on the surface of the Lu2O3 crystal sample in Example 1 of this invention. The arrows point to the grain boundaries.
[0025] Figure 3 This is an image of the etched morphology of the boundary region in the chemical etching-microscopic observation method of Example 1 of the present invention.
[0026] Figure 4This is a SEM image of the grain boundary region in the TEM analysis method of Embodiment 1 of the present invention.
[0027] Figure 5 This is a scanning electron microscope image of the cross-section of a TEM sample in the TEM analysis method of Embodiment 1 of the present invention.
[0028] Figure 6 This is a high-resolution TEM image of the boundary left side after it is straightened in the TEM analysis method of Embodiment 1 of the present invention.
[0029] Figure 7 This is a SAED diagram of the left region when the left side turns to the center in the TEM analysis method of Embodiment 1 of the present invention.
[0030] Figure 8 This is the SAED image of the two regions superimposed when the left side is turned to the center in the TEM analysis method of Embodiment 1 of the present invention.
[0031] Figure 9 The images shown are the right-side images after right-side alignment in the TEM analysis method of Embodiment 1 of the present invention; wherein, (a) is a high-resolution TEM image after right-side alignment, (b) is a SAED image of the right-side region when right-side alignment is achieved, and (c) is a SAED image of the two sides superimposed when right-side alignment is achieved.
[0032] Figure 10 The results show the surface roughness test results of the Lu2O3 crystal sample in Example 2 of this invention.
[0033] Figure 11 The results show the surface roughness test results of the Lu2O3 crystal sample in Comparative Example 1 of this invention.
[0034] Figure 12 The surface roughness test results of the Lu2O3 crystal sample in Comparative Example 2 of this invention are shown. Detailed Implementation
[0035] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0036] Example 1: Identification of grain boundaries in Lu2O3 crystals using direct diamond wire cutting method 1. Sample Preparation: The Lu2O3 crystal to be tested was cut using a diamond wire cutter to obtain the test surface. The wire diameter was 0.35 mm, the cutting speed was 0.25 mm / min, and the rotation speed was 260 rps. Roughness testing was performed using a surface optical profilometer. The surface roughness of the sample was Sa = 1.08 μm. The test results are as follows: Figure 1 As shown.
[0037] 2. Grain boundary identification: The sample surface to be tested is placed under bright light and moved left and right. Clear partitioning can be observed with the naked eye, with distinct boundaries, such as… Figure 2 As shown. This boundary is the grain boundary.
[0038] To verify the accuracy of this method, two original methods were used for validation: chemical etching-microscopy and TEM analysis.
[0039] Chemical etching-microscopic observation method: The crystal sample was placed in a 70 wt% phosphoric acid solution and etched at a specific temperature (160℃) for 15 min. After etching, the sample was removed and thoroughly cleaned with anhydrous ethanol and deionized water to remove residual acid. After drying, it was observed under an optical microscope. The boundary zone consisted of densely stacked pits with relatively straight edges, as shown in the image. Figure 3 As shown, the etch pits above the boundary zone exhibit clear equilateral triangles, while the etch pits below the boundary zone present as non-equilateral triangular depressions. The difference in pit morphology on both sides of the boundary indicates different crystal orientations on either side of the boundary, which is a grain boundary. Therefore, the method provided by this invention is accurate and feasible.
[0040] TEM analysis: The chemically etched sample was further cut and thinned using a focused ion beam scanning electron microscope (FIB-SEM). Figure 4 This is a scanning electron microscope schematic diagram of the grain boundary region, where the central bundle-like boundary line corresponds to the boundary of the etch pit after chemical etching. Figure 5 The cross-section of the sample after FIB cutting and thinning is shown. The hole and twisted vortex in the center of the sample are caused by the local stress release during the FIB thinning process. The sample after FIB thinning is placed on a copper grid. A clear boundary line can be clearly observed below the etch pit by TEM. The zone axis
[110] is determined by XRD reciprocal space calibration, and the rotation angle measurement accuracy is ensured by SAED origin correction function. The rotation angle of TEM is adjusted so that the two sides are turned to the crystal plane that is closest to the zone axis. The rotation angle of the two sides is recorded and the orientation difference of the two crystal planes can be obtained by calculation. The common closest crystal plane is found to be (222) plane after lattice spacing calibration. The region on the left side of the boundary is rotated to the (222) plane by TEM and then subjected to high-resolution TEM as shown. Figure 6 As shown, after rotation, the left side exhibits a regular lattice arrangement, while the right side shows an irregular arrangement, with significant differences in the lattice images on both sides. At this point, the SAED diffraction points in the left region are regularly arranged, as shown... Figure 7 As shown. Superimposing the electron diffraction patterns from the right region reveals that the diffraction spots do not completely overlap, resulting in two sets of diffraction patterns, as shown below. Figure 8As shown. Similarly, when the right-side region is rotated to the (222) plane, the right-side lattice exhibits a regular arrangement, while the left-side exhibits an irregular lattice arrangement. The SAED pattern diffraction points in the right-side region show a regular arrangement, while the superimposed diffraction points in the left-side region show an irregular arrangement, as shown. Figure 9 As shown in (ac). This disruption of lattice symmetry and diffraction spot symmetry directly proves that there is a certain orientation difference between the grains on both sides of the grain boundary. The rotation angles recorded when the left region is normalized are A1=2.46deg and B1=-1.69deg, and when the right region is normalized, the rotations are A2=-1.84deg and B2=4.98deg. Calculations determined the included angle between the two sides to be 7.93°, falling within the category of small-angle grain boundaries. Therefore, TEM observations confirm the accuracy and feasibility of the method provided in this invention.
[0041] Example 2: Identification of grain boundaries in Lu2O3 crystals by mechanical grinding and surface formation method 1. Sample Preparation: The Lu2O3 crystal to be tested was placed on the horizontal turntable of a grinder at 150 rpm. Aqueous Al2O3 abrasive with a particle size of 3 μm was added for wet grinding to obtain the test surface. Roughness was measured using a surface optical profilometer. The sample surface roughness Sa = 1.08 μm. The test results are as follows: Figure 10 As shown.
[0042] 2. Grain boundary identification: Place the sample surface under bright light and shake it from side to side. You can clearly observe the partitioning phenomenon with obvious boundaries. These boundaries are the grain boundaries.
[0043] Example 3: Identification of grain boundaries in Sc2O3 crystals using direct diamond wire cutting method 1. Sample preparation: The Lu2O3 crystal to be tested was cut into the test surface using a diamond wire cutter at a cutting speed of 0.25 mm / min, a wire thickness of 0.3 mm, and a rotation speed of 260 rps.
[0044] 2. Grain boundary identification: Place the sample surface under bright light and shake it from side to side. You can clearly observe the partitioning phenomenon with obvious boundaries. These boundaries are the grain boundaries.
[0045] Example 4: Identification of grain boundaries in Sc2O3 crystals by mechanical grinding and surface formation method 1. Sample preparation: The Sc2O3 crystal to be tested was placed on the horizontal turntable of a grinder at a speed of 150 rpm. Aqueous Al2O3 abrasive with a particle size of 4 μm was added for wet grinding to obtain the test surface.
[0046] 2. Grain boundary identification: Place the sample surface under bright light and shake it from side to side. You can clearly observe the partitioning phenomenon with obvious boundaries. These boundaries are the grain boundaries.
[0047] Example 5: Identification of grain boundaries in Y₂O₃ crystals by mechanical grinding and surface formation method 1. Sample preparation: The Y2O3 crystal to be tested was placed on the horizontal turntable of the grinder at a speed of 170 rpm. A water-based SiO2 abrasive with a particle size of 2 μm was added for wet grinding to obtain the test surface.
[0048] 2. Grain boundary identification: Place the sample surface under bright light and shake it from side to side. The partitioning phenomenon can be clearly observed with the naked eye, and there is a clear boundary. This boundary is the grain boundary of Y2O3 crystal.
[0049] Comparative Example 1: Observation of grain boundaries on the surface of Lu2O3 crystals with lower roughness 1. Sample Preparation: To investigate the effect of surface roughness on crystal properties, the crystal surface with identified grain boundaries in Example 1 was polished to achieve a surface roughness below 0.7 μm. Roughness testing was performed using a surface optical profilometer. The sample surface roughness Sa = 0.64 μm. The roughness test results are as follows: Figure 11 As shown.
[0050] 2. Grain boundary identification: When the sample surface to be tested is placed under bright light and moved from side to side, the original grain boundaries cannot be observed. This indicates that the angle difference of the reflected light generated on such a smooth surface is extremely weak, resulting in insufficient contrast between light and dark, and the grain boundaries of the crystal cannot be observed with the naked eye.
[0051] Comparative Example 2: Observation of grain boundaries on the surface of Lu2O3 crystals with higher roughness 1. Sample Preparation: For the crystals for which grain boundary identification was completed in Example 2, the crystal surface was polished with coarse sandpaper to increase the surface roughness to above 2 μm. Roughness testing was performed using a surface optical profilometer. The sample surface roughness Sa = 4 μm. The roughness test results are as follows: Figure 12 As shown.
[0052] 2. Grain boundary identification: When the sample surface to be tested is placed under bright light and shaken from side to side, the original grain boundaries cannot be observed. This indicates that the roughness is too large, causing the reflected light from all areas to be uniformly scattered in all directions. The entire surface presents a uniform, grayish matte finish. The reflection difference between grains is completely covered by strong background scattering, and the grain boundaries of the crystal cannot be observed with the naked eye.
[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for identifying small-angle grain boundaries in sesquioxide crystals, characterized in that, include: The sesquioxide crystals are machined to control the surface roughness to 0.7-2 μm; Place the crystal surface to be tested under a light source with an intensity of ≥500 lx and shake it. Observe with the naked eye; the boundary between the light and dark areas is the grain boundary. The crystal processing method includes: cutting along a direction parallel to the surface to be tested to obtain the sample to be tested, or performing wet grinding on the crystal to be tested to obtain the sample to be tested; The sesquioxide crystals include Lu2O3, Sc2O3, Y2O3, and their doped crystal systems.
2. The method as described in claim 1, characterized in that, The cutting is performed by diamond wire cutting with a wire diameter of 0.2-0.35 mm, a cutting speed of 0.2-0.3 mm / min, and a rotation speed of 260 rps.
3. The method as described in claim 1, characterized in that, The wet grinding speed is 100-200 rpm.
4. The method as described in claim 1, characterized in that, The particle size of the abrasive is 1-5 μm.
5. The method as described in claim 4, characterized in that, The abrasive is either silica abrasive or alumina abrasive.
Citation Information
Patent Citations
Method for judging grain boundary angle deviation in casting monocrystalline silicon and detection device
CN115560701A